Detecção Eletroquímica de Carbendazim em Sucos de Frutas Cítricas Utilizando Eletrodo de Pasta de Carbono - Elizabete Maria Maximiano; Claudia Andrea Lima Cardoso; Gilberto José de Arruda (Orbital: The Electronic Journal of Chemistry, 2016)
This paper describes a cheap and efficient simple electroanalytical method for determination of carbendazim in some citrus fruits juices: tangerine, lemon and orange. The electrode used was characterized electrochemically using cyclic voltammetry and square wave voltammetry, evaluating the response of the fungicide on the electrode surface. The electrochemical method for the determination of carbendazim was developed using the optimized conditions, obtaining a calibration curve in a linear range of 2.75 to 87.30 μg L-1 with a detection limit of 1,95 μg L-1. After constructing the analytical curve it was applied the proposed methodology in fruits obtaining recovery values between 93.3% and 99.1%. The obtained results show that citrus fruits commercialized in the local market are free of carbendazim.DOI: http://dx.doi.org/10.17807/orbital.v8i4.797